2011
DOI: 10.1038/nn.2990
|View full text |Cite
|
Sign up to set email alerts
|

Computational design of enhanced learning protocols

Abstract: Learning and memory are influenced by the temporal pattern of training stimuli. The mechanisms that determine the effectiveness of a particular training protocol are not well understood, however. The hypothesis that the efficacy of a protocol is determined, in part, by interactions among biochemical cascades that underlie learning and memory was examined. Previous studies suggest that the PKA and ERK cascades are necessary to induce long-term synaptic facilitation (LTF) in Aplysia, a neuronal correlate of memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
124
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(129 citation statements)
references
References 44 publications
4
124
1
Order By: Relevance
“…In Aplysia, however, maximal ERK1/2 activation occurred at ∼45 min after stimulation, which is much slower than our observations in rat sensory neurons. The synergistic activation of both kinases in Aplysia converges on transcriptional responses involving the cAMP response element-binding protein (CREB) (Zhang et al, 2012). Protocols that include properly timed stimuli have been developed to promote the interaction of PKA and ERK1/ 2, resulting in enhanced CREB phosphorylation and long-term potentiation (LTP) (Zhang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Aplysia, however, maximal ERK1/2 activation occurred at ∼45 min after stimulation, which is much slower than our observations in rat sensory neurons. The synergistic activation of both kinases in Aplysia converges on transcriptional responses involving the cAMP response element-binding protein (CREB) (Zhang et al, 2012). Protocols that include properly timed stimuli have been developed to promote the interaction of PKA and ERK1/ 2, resulting in enhanced CREB phosphorylation and long-term potentiation (LTP) (Zhang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The synergistic activation of both kinases in Aplysia converges on transcriptional responses involving the cAMP response element-binding protein (CREB) (Zhang et al, 2012). Protocols that include properly timed stimuli have been developed to promote the interaction of PKA and ERK1/ 2, resulting in enhanced CREB phosphorylation and long-term potentiation (LTP) (Zhang et al, 2012). An age-dependent increase of crosstalk between these kinases, as observed here, may therefore also reflect enhanced 'learning' capabilities of adult sensory neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al (2013) used small interfering RNA (siRNA) to reduce the basal level of CBP and impair LTF at sensory neuron-motor neuron (SN-MN) synapses of Aplysia. The mathematical model of Zhang et al (2012) was extended to include the cAMP/PKA and Raf/MEK/ERK pathways, as well as phosphorylation of CREB1, CREB2, and C/EBP. Simulations predicted training protocols that would compensate for the CBP deficit.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed aspects of the molecular and cellular mechanisms of LTM formation induced by repetitive training (8)(9)(10)(11), but how a single training induces a stable LTM is poorly understood (12).…”
mentioning
confidence: 99%